O impasse na política de preservação do patrimônio cultural em Fortaleza - Capasso, Marcelo Mota (2023)
The conservation of built cultural heritage has always been a problematic issue in Fortaleza. However, in the 2010s, the situation has taken a dramatic turn. Under entrepreneurial governance, the municipality apparently abandoned the conservation as a policy, relegating it to a completely residual condition in public management. The operational normative tools performance of local conservation policies has been undermined, reproducing deterioration, destruction and controversial physical interventions on historical landmarks all over the urban space. On the other hand, the municipality has been committed to a real state development agenda, by lightening limitations over urban management tools, whose practical effects point out to a close relationship with conservation policies’ apparent failure. Thus, the present study analyzes both policies frames under a relational approach, as a typical urban topic, in order to clarify what conservation deadlock is and how it took root.